Pengukuran Faktor Fisik K3: Kebisingan, Pencahayaan, Suhu dan Kelembapan di Lingkungan Kerja UKM Pengolahan Tahu Baso Kota Bogor - Ai Imas Faidoh Fatimah (Journal of Mandalika Literature, 2024)
Non-standard working environments can pose various hazards to workers, especially in SMEs. The potential hazards must be managed to protect workers’ safety and health, maintain product quality, and comply with applicable regulations. UKM XYZ produces processed meat products such as tofu meatballs and pempek. During the production process, the business owner has not conducted any measurement of potential hazards in the work environment. This study aims to measure and analyse the potential physical hazards in UKM XYZ. The research method used was observation and measurement of physical hazards on four variables, namely noise, lighting, and working climate, consisting of temperature and humidity. The data obtained was compared with the applicable occupational safety and health (OSH) standards. The results showed that noise levels were in accordance with the regulations because they were below the threshold limit value (TLV). Meanwhile, lighting, temperature, and humidity in the production room did not meet the TLV, potentially causing negative impacts on workers’ safety and health. UKM XYZ is recommended to take corrective actions on the ventilation system, lighting, provision of PPE, and installation of dehumidifiers. This research is expected to serve as a basis for the development of better occupational safety management in SMEs.